Karstrandebene und Poljeboden: Zur Frage der Entstehung von Einebnungsflächen im Karst - Kayser, Kurt (ERDKUNDE, 1955)
The fact that under certain specified conditions karst denudation may reach the final stage of complete peneplanation is, according to the author, not sufficient justification for acknowledging the validity of the cycle theory for karst areas as is done by P. Birot. The depenence of the possibilities for the formation of planation surfaces on strictly localized conditions, emphasized previously (1934), is referred to, and the necessity of distinguishing the extensive land surfaces of the pre-karst relief in the Dinaric Karst and the karst planations proper is underlined. These latter can only develop on the karst margins or on the floors of still functioning i. e. periodically flooded poljes. The author is of the opinion that for the further development of the marginal karst planations and polje floors suitable conditions are still presented by the present climate and that therefore they must by no means be looked at as fossil landforms as was done by C. Rathjens. Nevertheless the sections of the polje floors which are still capable of active widening are continuously becoming more and more restricted due to the increasing degeneration of the underground karst hydrography, as described by O. Lehmann, which is associated with a fall in the local base level. For the same reasons some former marginal karst planations have become fossilized. It may be assumed that the climatic conditions of the Pliocene Period (Lower to Middle Pliocene) favoured the formation of planation surfaces but more detailed investigations are still needed to support this theory. Similarly, the concept that the Dinaric Karst - inselberge have arisen from a tropical cone karst (Kegelkarst) has not been satisfactorily proved.